Transport and fate of 137Cs in the Mediterranean and Black Seas system during 1945–2020 period: A modelling study. (November 2019) - Bezhenar, R.; Maderich, V.; Schirone, A.; Conte, F.; Martazinova, V.
Abstract: The compartment model POSEIDON-R with an embedded dynamic food web model was used to assess 137 Cs distributions in the Mediterranean and Black Seas during 1945–2020 due to the weapon testing and accident at the Chernobyl nuclear power plant. Three maximums of contamination of surface waters can be identified from 1950 in the Mediterranean Sea system. Two of them (in 1959 and 1963) were caused by atmospheric deposition due to the nuclear weapon testing. Third maximum in 1986 was related with the Chernobyl accident. Maximum of inventory of 137 Cs in the Mediterranean Sea (11461 TBq) was achieved in 1968, whereas secondary maximum caused by Chernobyl accident in 1986 was almost the same (11460 TBq). The corresponding maximum in the Black Sea (3703 TBq) was reached in 1986. It is approximately two times larger than nuclear weapon tests maximum. The results of simulations conducted with generic parameters agreed well with measurements of 137 Cs concentrations in the water, bottom sediments, and in marine organisms. The inventory in the Mediterranean Sea is most sensitive to the global deposition, whereas water exchange with Atlantic Ocean and the Black Sea plays minor role. The cumulative individual dose for the period 1945–2020 from consumption of marine products contaminated by 137 Cs was in the range 41–130 μSv in the Mediterranean Sea and 213–274 μSv in the Black Sea. The dose increased up to 40% due to Chernobyl accident in the Mediterranean countries and 66–103% in the Black Sea countries comparatively with dose from the global deposition. A useful application of the modelling for monitoring purposes was selection of representative regions in the Mediterranean Sea (5 regions) and in the Black Sea (4 regions) using "etalon" method for classification. Highlights: A box model with a dynamical food chain model was applied to Southern European Seas. Transport and fate of 137 Cs were simulated for major sources of activity in the 1945–2020. Simulated concentrations in the water, sediments and biota agree with observations. Inventories of 137 Cs in the water and bottom sediments were estimated. The global deposition is a major source in the Mediterranean Sea.